Perancangan Sistem Monitoring Tanaman Strawberry Di Dataran Rendah Menggunakan Aplikasin Berbasis IoT - Yusuf Anwar Marganing Putra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
A system for monitoring optimal temperature through automatic fan cooling and watering for strawberry plants in lowland areas has been developed using IoT-based Bylink application with prototyping method to improve plant productivity in the area. The prototyping method was used to design a more optimal temperature monitoring system with the addition of IoT technology and Bylink application, which can facilitate effective and efficient plant monitoring and maintenance. The temperature monitoring system is equipped with temperature sensors connected to the internet network through IoT technology. In this system, the Bylink application is used to facilitate monitoring and adjustment of optimal air temperature for strawberry plant growth. Furthermore, the system is also equipped with automatic fan cooling and watering system that can be controlled through the application, making it easier for farmers to monitor and maintain plants more effectively and efficiently. The research was conducted by considering factors affecting strawberry plant growth and the use of IoT technology and Bylink application in system development. Testing and evaluation were carried out to ensure that the tool can function well and meet the requirements. The results showed that the system design can help farmers improve plant productivity and facilitate plant monitoring and maintenance. This system can be an alternative to increase strawberry plant production in lowland areas.